Winning space for conservation: the growth of wildlife conservancies in Kenya - Bashir, Munira Anyonge; Wanyonyi, Edwin (Frontiers in Conservation Science, 2024)
Kenya’s conservation areas consist of national parks and reserves, national forests, and private and community wildlife conservancies. The historically protected areas only account for 10% of Kenya’s land mass (national parks, reserves, and protected forests). Conserving Kenya’s biodiversity referred to as a “national heritage” is at the core of the country’s conservation agenda. The success of Kenya’s model of free-ranging wildlife is based on allowing as much unhindered movement and distribution of wildlife as possible. However, the human population increase, along with the expansion of agriculture into arid lands and the impacts of climate change, has affected the dynamics of pastoralism, where increased competition for natural resources has escalated in some areas. One of the identified measures to mitigate the current challenges is to increase the space for conservation and provide incentives for communities to conserve. The development and growth of the wildlife conservancy movement in Kenya have been a prominent response. As of 2023, there have been 230 wildlife conservancies in Kenya totaling 9.04 million ha and comprising 16% of Kenya’s total land mass (with 195 being members of the Kenya Wildlife Conservancies Association). To contribute to the global target of protecting 30% of lands, freshwaters, and oceans by 2030, the Kenyan Government considers the expansion of the number and area of wildlife conservancies as an important mechanism to achieve these targets. Here, we discuss Kenya’s wildlife conservancies from legal and policy perspectives, the factors that have enabled their growth, the challenges they face, and the opportunities ahead.